Seroprevalence of Scrub Typhus in Patients Attending Dhulikhel Hospital, Kavre - Madhup, S. K.; Shrestha, R.; Katuwal, N.; Magar, S. R.; Shrestha, S.; Bhandari, S.; Tamrakar, D. (Kathmandu University Medical Journal, 2021)
Background Scrub typhus is a largely ignored tropical disease and a leading cause of undifferentiated febrile illness. It is caused by Orientia tsutsugamushi. Scrub Typhus is frequently observed in South Asian countries. However, clear epidemiological information of this disease is lacking in case of Nepal. Nepal has shown steady increase in cases of Scrub Typhus since 2015. The epidemiological data related to this disease would support the decision making and surveillance design for early outbreak detection and immediate responses including prevention and treatment of scrub typhus in Nepal. Objective To understand prevalence of Scrub Typhus in subjects who had visited outpatient department at Dhulikhel Hospital. Method In this study, we have studied antibody test data (n=784) for Scrub Typhus from 2019 to 2021. The tests were performed on serum samples of patients who had visited OPD at Dhulikhel Hospital with fever lasting more than 5 days. The kit used in analysis was Scrub Typhus Detect™ IgM ELISA Kit from InBios International. Result Out of the total subjects (n=784), 133 were positive (16.9%) for IgM antibody of Scrub Typhus. The positivity in female (18.6%) was higher than the male subjects (15.3%). The positivity rate was variable among the different age groups, with highest positivity for age group 0-14 years (25%). The seasonal variation was also observed among the seropositive cases. Conclusion Scrub Typhus being a neglected tropical disease has high prevalence. It can be postulated that female subjects and subjects of age group 0-14 years are vulnerable to the infection with Scrub Typhus. There is need to increase the surveillance of Scrub Typhus to add the knowledge for diagnosis and treatment.